Meeting Review – Helicobacter pylori: Basic Mechanisms to Clinical Cure 2000. (1st November 2000) - Lahaie, Raymond G; Chiba, Naoki; Fallone, Carlo
Abstract : The meeting Helicobacter pylori : Basic Mechanisms to Clinical Cure 2000, held in Bermuda from March 26 to 29, 2000, gathered physicians and scientists from all corners of the world. State-of-the-art reviews and the most recent developments in the field were presented. This article summarizes the highlights of this meeting, including important scientific and clinical developments.